Eastern Democratic Republic of the Congo on the way to peace? War remembrances, post conflict discourse construction: a discursive analysis of Djungu-Simba's novellas - Kaputu, Felix A. (Afrika Focus, 2014)
Throughout the history of the Democratic Republic of the Congo, various writings – literary, sociological, and political – retrace the challenges that have faced the nation: colonialism, access to independence, postcolonial failures, wars, dictatorships and female exploitation. Some historians, sociologists, literary critics and journalists touted the successes of colonial times and the first Republic, especially those who worked for these governments. Other essential voices remained silent, in order to avoid dictatorial repression and censure, especially under President Mobutu. With the arrival of Laurent Kabila, freedom of speech brought forth discourse that slowly deteriorated into insincere rhetoric and, finally, utter silence. In Les Terrassiers de Bukavu: Nouvelles, Charles Djungu-Simba, the editor of several Bukavu Congolese novella writers, predicts that the socio- political discourse put forth in such narratives will lead to chaos followed by further repression that will continue the cycle presented all along these metanarratives unless oppression is radically addressed from the grassroots. Key words: Bukavu, violence discourse, war, apocalyptic myth, UN Forces, Democratic Republic of the Congo, novellas